Phytoreduced gold nanoparticles from vitalmelon promote white adipocyte browning in murine cells by targeting phospholipase D2 - Sun Young Park; He mi Kang; Kangmin Park; Lu Guo; Jin-Woo Oh; Geuntae Park; Nam Jun Kang; Young-Whan Choi (Journal of Photochemistry and Photobiology)
Recent advancements in green nanotechnology have enabled the synthesis of nanoparticles using natural resources, thereby offering ecofriendly alternatives for various biomedical applications. In this study, we report the biosynthesis of gold nanoparticles (GNPs) using vitalmelon (VW) extract (VW-GNPs) without the need for stabilizers or surfactants. The VW extract served as a reducing and a stabilizing agent. The synthesized VW-GNPs were characterized by UV–Vis spectroscopy, dynamic light scattering, Fourier-transform infrared spectroscopy, high-resolution transmission electron microscopy, and energy-dispersive X-ray spectroscopy. The results revealed successful synthesis of VW-GNPs with an average size of 35.41 ± 2.37 nm and a zeta potential of -28.16 ± 1.01 mV, indicating good stability. The biological activity of VW-GNPs was evaluated in lipogenesis and browning of differentiating white adipocytes, focusing on their effects on lipid droplet formation, mitochondrial biogenesis, and expression of browning markers such as UCP1, PRDM16, and PGC1α. VW-GNPs significantly reduced lipid accumulation in fully differentiated 3T3-L1 adipocytes and promoted the conversion of white adipocytes into metabolically active beige adipocytes. Moreover, VW-GNPs enhanced mitochondrial biogenesis, which is crucial for energy expenditure in beige adipocytes. Further investigation using pharmacological inhibition and knockdown experiments revealed that phospholipase D2 inhibition synergistically promoted the browning effects of VW-GNPs. These findings suggest that VW-GNPs represent a promising novel therapeutic strategy to combat obesity by modulating adipocyte metabolism and increasing energy expenditure via adipocyte browning.